The Role of De facto Circumstances in Understanding the Religion = دور الواقع في فهم الدين - Khan, Musaddiq Majid (Department of Islamic Studies, University of the Punjab, Pakistan, 2015)
It is an established fact that Islam is a complete code of life that can respond to the dynamic and diversified changes in a modern era. The customs, habits, cultures, traditions are no doubt essentials of human life and play vital role in smooth and good functioning of societies. Islam is not a static or stagnant religion but it considers societal changes positively. However it has its some principles that are the foundation stones to construct any new structure to deal with new challenges religiously. Islam is a dynamic religion but this doesn’t mean that it can absorb each and every thing of modern life without filtration. Islamic juristic system is based on solid grounds and it deals religion and human life parallel. The core principles of Halal and Haram never changes or amended but are relaxed at optimal level where chronic situation evolves. Hence this is the need of the day to understand the modern era with its pros and cons to issue legal Islamic verdicts. Islam gives pragmatic approach and deals situations with its permanent rules.